A crucial first randomized controlled trial of thymectomy in nonthymomatous myasthenia gravis - Bourque, Pierre R.; Chardon, Jodi Warman (Journal of Thoracic Disease, 2016)
The much awaited results of a randomized trial of thymectomy in myasthenia gravis (MG) were published in the August 11, 2016 edition of New England Journal of Medicine by Wolfe et al. on behalf of the “Thymectomy trial in non-thymomatous myasthenia gravis patients receiving prednisone therapy” (MGTX) study group (1). This landmark publication stands as the only controlled randomized thymectomy trial, hoping to end a 75-year-old controversy.